PENGEMBANGAN MEDIA PEMBELAJARAN PELINFO BERBASIS ANDROID PADA MATERI INFORMATIKA UNTUK SISWA KELAS X AKUNTANSI SMK NEGERI 2 BUDURAN - Nizhomy, Adeb; Dharu Wahyu Pambudi, Achmad Tirta; Ubaidillah, Achmad; Yulianto, Achmad; Dinar Lestari, Adhinda; Karna Wicitra, Adi; Sondang Sumbawati, Meini; Setya Budi, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The advancement of technology has driven transformation in education, including the need for interactive learning media that aligns with industry demands. At SMK Negeri 2 Buduran, Informatics learning for 10th-grade Accounting students remains conventional, with limited digital teaching materials supporting Project-Based Learning (PJBL). This results in low student engagement and difficulties in developing practical skills. This study aims to develop an Android-based learning media called PELINFO using Unity to facilitate interactive, project-based learning. The research method employs Research and Development (R&D) with the Waterfall model, covering stages of needs analysis, design, development, testing, and implementation. The app's feasibility was tested through a Likert-scale questionnaire administered to 38 students. The results showed a 99.26% feasibility rate (categorized as Highly Feasible), with the majority of respondents providing positive feedback on interface design, ease of use, and learning benefits. PELINFO successfully integrates theoretical material with PJBL project guidance, featuring multimedia elements and self-assessment tools. Its implementation enhances active student participation and contextual understanding of Informatics concepts. This study proves that technology-based media development can be an effective solution for adaptive, practice-oriented vocational learning. Future recommendations include adding online collaboration features and refining content based on the latest curriculum.